Association Between Metabolic Syndrome and Risk of Endometrial Cancer - Abdulrahman, Rena Ghassan; Ramadan, Lina Salman; Yosef, Ahmad Hasan (Journal of medical and pharmaceutical sciences, 2021)
Background: Endometrial cancer is one of the most common cancers of the female reproductive system, and it is one of the rise globally. metabolic syndrome is a clustering of at least three of the five following medical conditions: central obesity, diabetes, hypertension, high serum triglyceride and low serum high density lipoprotein.Aim: The aim of this study was to assess the association between the metabolic syndrome and the endometrial cancer.Methods: this case control study comprised of 93 patients with abnormal uterine bleeding admitted to department of obstetrics and gynecology, Tishreen University Hospital, Lattakia Syria, during the period of February 2019 To February 2021, patients who full field the inclusion criteria for the study were divided into 2 groups, the first consisted of 31 patients had endometrial cancer with histological confirmation (cases).The second consisted of 62 patients with normal biopsies (controls).The determination of the metabolic syndrome is according to NCEP ATP III(2005)Results: Baseline characteristics were matched in both study groups.In assessment the association between the metabolic syndrome and the endometrial cancer the odd ratio (OR) was (3.31). the odd ratio (OR) for metabolic syndrome (MS) elements were (2.9 with diabetes, 3.9 with obesity, 2.05 with hypertension, 2.36 with high triglyceride and 1.2 with low high density lipoprotein).Conclusion: the metabolic syndrome and its elements are causes of endometrial cancer.
Keywords: Endometrial Cancer (EC); Metabolic Syndrome (MS); abnormal uterine bleeding